2020
DOI: 10.1016/j.jinf.2020.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin converting enzyme genotypes and mortality from COVID-19: An ecological study

Abstract: Highlights Angiotensin converting enzyme (ACE) genotypes may influence COVID-19 mortality. II genotype frequency was significantly associated with decreased mortality. Association between increased mortality and DD genotype frequency was not detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 26 publications
3
33
0
1
Order By: Relevance
“…Contrary to these results, increased frequency of the I/I genotype was inversely correlated with susceptibility to SARS‐CoV‐2 infection and consequent mortality in European and Asian countries (Yamamoto et al, 2020). Similarly, an ecological study reported that increased I/I genotype frequency was significantly associated with decreased Covid‐19 mortality in 25 countries from different geographical regions of the world (Aung et al, 2020).…”
Section: Angiotensin‐converting Enzymesmentioning
confidence: 95%
“…Contrary to these results, increased frequency of the I/I genotype was inversely correlated with susceptibility to SARS‐CoV‐2 infection and consequent mortality in European and Asian countries (Yamamoto et al, 2020). Similarly, an ecological study reported that increased I/I genotype frequency was significantly associated with decreased Covid‐19 mortality in 25 countries from different geographical regions of the world (Aung et al, 2020).…”
Section: Angiotensin‐converting Enzymesmentioning
confidence: 95%
“… 1 In COVID-19 infection, the renin-angiotensin system (RAS) pathway is thought to play an important role in the development of ARDS and aggravation of the clinical picture. 2 Theoretically, in COVID-19, the angiotensin-converting enzyme-1 (ACE1)/angiotensin-converting enzyme-2 (ACE2) balance is disturbed due to overexpression of the ACE1 receptor and down-regulation of the ACE2 receptor. Disruption of this balance results in excessive RAS activation, and lung damage occurs with excessive production of angiotensin II.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of evidence supports a relationship of ACE I/D polymorphism and clinical outcome of ARDS [ [302] , [303] , [304] ]. ACE I/D polymorphism appears to be also associated with the severity of ARDS in patients infected with SARS-CoV or SARS-CoV-2 [ 135 , 302 , 303 , [305] , [306] , [307] ]. Analysis of patient cohorts infected with SARS-CoV and SARS-CoV-2 suggests that polymorphism in ACE2 is not associated with the clinical outcome of ARDS [ 305 , 308 , 309 ].…”
Section: The Roles Of Ace2 and Angiotensin II In Coronavirus-induced mentioning
confidence: 99%